Challenges in Transitioning from a Unified Accounting System to International Financial Reporting Standards: The Case of Kurdistan, Iraq - Khudir, Ibrahim (Auckland University of Technology, 2021)
This dissertation investigates the primary factors affecting Kurdistan to transition from the current accounting system to International Financial Reporting Standards (IFRS) and the challenges ahead. It examines the challenges of the use of IFRS in Kurdistan to prepare corporate financial statements. International institutions have played a vital role in the development of Kurdistan's economy, particularly in the natural resources sector. Hence, accounting practices have been under internal (regulations) and external (international institutions) pressures to follow international accounting standards. Document analysis has been used employing institutional theory to identify the factors and challenges. The results reveal that the decision to implement IFRS in Kurdistan is based on the three forms of institutional isomorphism. From the analysis, it has been observed that external pressures from the World Bank and international accounting bodies are stronger than internal pressures. In this regard, the government is a key player in making the final decision of IFRS adoption in the region. The result shows that there are several challenges one set of which originated from Kurdish practitioners not being able to adopt IFRS. Further, this study provides evidence that the decision to adopt IFRS is mainly influenced by efforts to achieve international financial support and promote economic trade. The study suggests that Kurdistan can stay in the current accounting system and implement IFRS gradually. This study is appropriate for academics, professionals, and accounting researchers with an interest in Kurdish accounting practice. Also, the findings of the study will be useful for the Kurdish government and countries that plan to implement IFRS.
Keywords: Kurdistan; Accounting system; IFRS; Institutional Theory; Institutional isomorphism